Peculiarities of marginal analysis in decision-making - Оралбаева, Ж.; Еспанова A. (Journal of Economic Research & Business Administration, 2017)
The article describes the features of the use of marginal analysis to make effective management decisions, presents the main features and stages of marginal analysis. Margin analysis helps to trace the relationship between such important economic indicators such as costs, production volume and profits, it is a key factor in the decision of many management decisions. For operational decision-making on the normalization of the financial condition of the organization is necessary to organize separate accounting of fixed and variable costs for product types and for the whole organization. This creates the prerequisites for long-term analysis of the development of different options for profit. The world economic practice is considered to be cost control system that integrates accounting, analytical and managerial procedures. Marginal analysis allows management or managers of organizations to reliably estimate the current situation and prospects.